Correlation of caries occurrence in primary teeth using human leukocyte antigen typing and maternal and physiochemical factors - Shraddha Saikia; Shivani Mathur; Manvi Malik; Nikita Gulati (Wolters Kluwer Medknow Publications, 2022)
Background: Dental caries being the leading health issue worldwide has no specific cure due to its multifactorial etiology and genetic susceptibility. Hence, this paper attempted to correlate the clinical and hereditary factors between mother and child, to predict the caries occurrence in child in future, and thereby implement early preventive measures. Aim: The aim of the study was to look for an association between maternal and child's human leukocyte antigen (HLA)-DR4 levels and relate it with other physiochemical factors to assess caries susceptibility in children. Methodology: Saliva samples were collected from children who were in the age group of 0-6 years and their mothers by spitting method and swab method. The clinical indicators such as Decayed, Missing, and Filled Teeth, decayed, extraction needed, and filled teeth, salivary flow rate, and pH were recorded by clinical evaluation. The Streptococcus mutans count was measured by culture plate followed by colony count method, and the HLA-DR4 factor was assessed using ELISA. Results: The results revealed a statistically significant correlation between the physiochemical factors of the mother and the child. The genetic factor in which the HLA-DR4 caries indicator was checked also has a strong association between the mother and the offspring. Thus, a strong caries prediction formula was derived through which probability of caries occurrence in the child could be determined prematurely. Conclusion: Thus, it can be concluded that using the clinical and genetic factors, the caries prediction can be done for the child and preventive protocol can be started before disease occurrence.